2006
DOI: 10.1007/s10620-006-9227-9
|View full text |Cite
|
Sign up to set email alerts
|

Primary Coloduodenal Fistula in a Patient with Crohn's Disease

Abstract: The posterior surface of the proximal transverse colon and the anterior surface of the descending duodenum are intimately related, predisposing to fistulization in this area. We herein describe a rare case of benign duodenocolic fistula secondary to Crohn's disease. We emphasize the clinical presentation with fecaloid vomiting, as well as the establishment of the diagnosis by endoscopy, which are both extremely rare. The presence of a colonic stricture supports the hypothesis that the disease started in the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 24 publications
1
20
0
Order By: Relevance
“…Reports of the surgical management of patients with GSD-1b complicated by colitis and coloduodenal fistula are rare and mostly case reports[ 4 , 11 ]. For our patient, we performed primary excision of the coloduodenal fistula followed by primary repair of the duodenal defect.…”
Section: Discussionmentioning
confidence: 99%
“…Reports of the surgical management of patients with GSD-1b complicated by colitis and coloduodenal fistula are rare and mostly case reports[ 4 , 11 ]. For our patient, we performed primary excision of the coloduodenal fistula followed by primary repair of the duodenal defect.…”
Section: Discussionmentioning
confidence: 99%
“…In most cases the fistulas arise from the diseased small or large bowel. Pain located in the epigastrium in association with nausea and vomiting are the most common symptoms, while fecal vomiting is rare [3,6,7]. Contrast imaging studies (barium enema or meal and small bowel series) and endoscopy are the most useful procedures for the diagnosis and evaluation of the fistulas [7].…”
Section: Discussionmentioning
confidence: 99%
“…Resection of the diseased segment of the bowel containing the fistula (primary site of the disease), resection of the fistula and primary repair of the affected organ, has been proven so far to be the most effective treatment method of intra-abdominal fistulas and numerous operative approaches have been suggested [3,6,10,14]. In our patient right hemi-colectomy with ileo-transverse anastomosis, drainage of the abdominal abscess and primary closure of the upper GI tract openings (gastric, duodenal and jejunal) were performed at one stage operation, without postoperative complications.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of stenosis and deformity of the stomach and duodenum could be observed in the late stage of CD and it can lead to gastrointestinal tract obstruction [9]. Duodenal fistulas are very rare [9], although El-Hajj II et al reported a case of primary duodeno-colic fistula, surgically treated, due to CD [26].…”
Section: Leki Stosowane W Terapii Choroby Leśniowskiego-crohnamentioning
confidence: 99%